Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 8 - Section 8.2 - Introduction to Functions - Practice: 16

Answer

$f$($x$) = $3x^{2}$ - $x$ + 2; when $f$(2) $f$(2) = 12

Work Step by Step

$f$($x$) = $3x^{2}$ - $x$ + 2; when $f$(2) First replace $x$ with 2 $f$(2) = $(3 \times2)^{2}$ - 2 + 2 Next multiply the terms in (*), and drop (-2 + 2) because it equals 0 $f$(2) = $6^{2}$ Finally multiply $6\times6$ $f$(2) = 12
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.